1998
DOI: 10.1111/j.1572-0241.1998.092_c.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Simplification of 13C-Octanoic Acid Breath Test for Gastric Emptying of Solids

Abstract: The 13C-octanoic acid breath test for gastric emptying of solids is as reproducible as scintigraphy. A subset of 11 sampling times provides sufficient information to characterize the whole breath-test curve, but the sampling period should be extended to 6 h after dosing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
46
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(59 citation statements)
references
References 12 publications
9
46
1
3
Order By: Relevance
“…Several studies [14][15][16][17] have found a significant correlation between this breath test and scintigraphy, which is the standard method for measuring the gastric emptying rate, and the 13 C-octanoic acid breath test is now considered a reliable and simple test for assessing gastric emptying. 13,[18][19][20][21][22] Several studies evaluating gastric emptying in patients with CRF have yielded conflicting results; in some of these, 1,3,5 gastric emptying was found to be delayed, while in others [23][24][25] it was unchanged, when using scintigraphy. Two studies 2,4 have shown delayed gastric emptying in patients with CRF, using real-time ultrasonography and the 13 C-octanoic acid breath test.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies [14][15][16][17] have found a significant correlation between this breath test and scintigraphy, which is the standard method for measuring the gastric emptying rate, and the 13 C-octanoic acid breath test is now considered a reliable and simple test for assessing gastric emptying. 13,[18][19][20][21][22] Several studies evaluating gastric emptying in patients with CRF have yielded conflicting results; in some of these, 1,3,5 gastric emptying was found to be delayed, while in others [23][24][25] it was unchanged, when using scintigraphy. Two studies 2,4 have shown delayed gastric emptying in patients with CRF, using real-time ultrasonography and the 13 C-octanoic acid breath test.…”
Section: Discussionmentioning
confidence: 97%
“…Although scintigraphy is usually considered to be the reference method for measuring gastric emptying in humans, several drawbacks (e.g., equipment, irradiation) limit its application in routine practice. On the other hand, breath tests correlate very well with scintigraphy (35,(45)(46)(47)(48). We used a formula method to determine the outcome parameters that reflects the biphasic nature of gastric emptying and allows calculation of the lag phase and rate of emptying for both solids and liquids (20,21).…”
Section: Control Cm3mentioning
confidence: 99%
“…In the past few years, the most popular tests have been the scintigraphic method and the breath test (9,10,13,36). These methods have also been used in animal studies (4,9,47).…”
mentioning
confidence: 99%